Pengaruh Strategi Inside Outside Circle terhadap Hasil Belajar IPA Siswa Kelas III SD Negeri101901 Lubuk Pakam - Nuri Ramadhan; Leni Malinda; Nurdana Naina (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This research aims, the objectives of this research are as follows: (1) to find out how much influence the inside outside circle learning strategy has on the science learning outcomes of Class III at SD Negeri 101901 Lubuk Pakam, (2) to find out student learning outcomes on green plant material in science subjects for class III students at SD Negeri 101901 Lubuk Pakam This type of research uses a quasi-experimental quantitative approach. This research was conducted at SD Negeri 101901 Lubuk Pakam using two classes of 20 students each consisting of an experimental class and a control class. This research was conducted using pretest and posttest questions. The results of research carried out in the experimental class and control class show that the experimental class which used the inside outside circle learning strategy got the highest score, namely 92 and the control class which used the true or false strategy got the highest score of 88. So it can be seen how big the influence of the inside learning strategy is. outside circle on the results of class III science learning at SD Negeri 101901 Lubuk Pakam.